THE ANALYSIS OF INDIVIDUAL SKILLS OF ICE SLEDGE HOCKEY PLAYERS AT THE TORINO 2006 PARALYMPIC TOURNAMENT - Kudláček, Martin; Dalbesio, Isabella; Janečka, Zbyněk; Vanlandewijck, Yves; Beckman, Emma (European Journal of Adapted Physical Activity, 2009)
Ice Sledge Hockey is one of the fastest growing winter Paralympic sports. There has been little research performed on ice sledge hockey and consequently the  information on performance parameters is scarce. The purpose of this study is to determine the differences in the level of individual ice sledge hockey skills among players of eight teams participating in Paralympic tournament Torino 2006 using observation protocol for assessment of key technical skills in Ice Sledge Hockey (Beckman, Kudláček & Vanlandewijck, 2007). The players involved in this study were players from Paralympic tournament. Four of the five best players are from Canada and one is from Norway. While we presented clear differences of individual players which are associated with actual standings in the Paralympic tournament we found only significant differences are total scores (F=5.29, p0.01) and skating subscale (F=3.66, p0.05).
Keywords: Disability sport; skills; observation protocol; skating; passing; shooting; checking